Karakteristik Pergerakan Pekerja Kawasan Industri Rambut di Jalan Jend. A.Yani Kabupaten Purbalingga - Hardini, Probo (Jenderal Soedirman University, 2010)
Activity of land use at roadside oftentimes generates trouble in the form of resistance that cause to road and streetÂ performance. Hair industries at Jalan Jend. A. Yani caused friction side that influence street performance. This research identify hair industryâs worker characteristic by questioner method. The result tell us how distance influence ammount of worker. Mode preference of worker is influenced by their total revenue and gender. In gender case, thereâs nothing can influence mode choice for man. But in woman side, travel time and distance influence mode choice. We knew that worker movement is short movement from their choices of mode andÂ their transport cost. This research is conducted to supply worker mass transport in order to reduce their movement acvitiy effect, especially for A. Yani street performance.